Der Paradox Eine : antignostischer Monarchianismus im zweiten Jahrhundert - Hübner, Reinhard M. (Vigiliae Christianae, Supplements, 1999)
These essays propose a new dating of, and historical setting for the letters of \'Ignatius of Antioch\'. In so doing this volume forms an important contribution to the study of Monarchianism and early church history as well. An examination of the fragments of Noëtus of Smyrna, the founder of Monarchianism, leads to the discovery of the oldest Regula fidei , and of its origin as part of anti-gnostic polemics. On the ground of late second-century parallels, especially Melito and Irenaeus, this Regula can be dated between 160 and 180 CE. It is within this context that the so-called Letters of Ignatius fit seamlessly. As a result of these findings this volume argues for a significant revision of our understanding of early church history. Monarchianism (\'Sabellianism\', \'Patripassianism\'), later considered heretical, is shown to have been the almost universally accepted belief within the Church up to the period of the Roman bishops Zephyrinus and Callistus.